Systematic Review : Violation of Integrity from the Perspective of Psychology, Organizational Context and Community Culture - Idha Rahayuningsih; Fendy Suhariadi; Cholichul Hadi (Universitas Ahmad Dahlan, 2020)
AbstractThe report on the crackdown on ICW corruption cases in 2019 explained that during 2019 there were 271 cases in Indonesia, as many as 29 (10.7%) cases occurred at the national level and 242 (89.3%) occurred in various regions in Indonesia. These data indicate the existence of integrity violations committed by public officials. The purpose of the literature review is to explore the psychological, organizational, and cultural factors of society that affect integrity violations. Research methods are systematic reviews. The results of the literature review: 1) psychological factors include low universal basic values and virtues, low moral judgment, low risk perception, low shame and guilt, high love of money, high machiavellianism, external motivation, authority, wealth, status and affiliation motivation, luxurious and hedonistic lifestyle and low happiness; 2) organizational factors are quite varied, including an ethical climate that is perceived negatively and self-oriented, less transparent organization, Human Resources and performance systems, politicization of the bureaucracy, the role model of the leader / superior is not good, several other factors; 3) Community cultural factors include high power distance, high masculinity, high collectivism and avoiding low uncertainty.Key Word : Violation of Integrity, Psyhology, Organizational Context, Community Culture